2016
DOI: 10.12681/ppej.9873
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Studies Examining the Impact of the Interactive Whiteboard on Teaching and Learning: what we do learn and what we do not

Abstract: Summary. This systematic review focuses on the impact of Interactive Whiteboards (IWBs) on teaching and learning. Learning is interpreted through a Vygotskian constructivist lens, emphasizing quality through dialogic interaction. Classroom interactions and achievement in standardized tests are considered formative and summative assessment tools, respectively. Thus, our aim was to investigate whether the IWB technology had any effect on teaching and learning, reflected in standardized forms of testing or in-cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…According to the participants' responses, students used the dynamic demonstration of systems, texts, and images to clarify their thinking, to demonstrate their understanding, to support their reasoning, and to teach other students. Confirming the study results, Kyriakou and Higgins (2016) stated IWBs affected summative assessments and classroom talk and suggested enhancing the theoretical framework. They also added the notion that the summative assessments offer considerable insights into students' learning.…”
Section: What Are the Experiences Of Elementary Teachers In Integrating Interactive Whiteboards In Their Classrooms?supporting
confidence: 70%
“…According to the participants' responses, students used the dynamic demonstration of systems, texts, and images to clarify their thinking, to demonstrate their understanding, to support their reasoning, and to teach other students. Confirming the study results, Kyriakou and Higgins (2016) stated IWBs affected summative assessments and classroom talk and suggested enhancing the theoretical framework. They also added the notion that the summative assessments offer considerable insights into students' learning.…”
Section: What Are the Experiences Of Elementary Teachers In Integrating Interactive Whiteboards In Their Classrooms?supporting
confidence: 70%
“…After 2 years, the effects were almost zero in all subjects (þ.02 for English, .00 for mathematics, and À.03 for science; Higgins et al, 2005). A systematic review conducted by Kyriakou and Higgins (2016) found similar results, with the use of IWB revealed to impact on neither students' level of attainment nor the quality of classroom learning.…”
Section: Introductionmentioning
confidence: 82%
“…Concerning the empirical evidence, we will refrain in the following from describing the studies that contribute to the current state of research in detail, since these studies are already summarized and discussed in a recent meta-analysis as well as in a critical review (cf. Kyriakou & Higgins, 2016;Shi et al, 2021). Based upon these latter two research overviews, we will provide the gist of the current state of research.…”
Section: The Impact Of Interactive Whiteboards On Motivation and Lear...mentioning
confidence: 99%
“…Though, the empirical evidence is not that straightforward for at least two reasons: First, the current research situation with respect to the impact of the IWB on learning is still rather sparse, with only a few published (quasi)-experimental studies in this research field (see Mariz et al, 2017;Shi et al, 2021). Second, several studies exist that do not show a beneficial effect on learning success (e.g., Albaaly & Higgins 2012;Shi et al, 2018; for a critical review, see Kyriakou & Higgins 2016). This calls for further studies that aim at being able to paint a more accurate picture if, when, for whom and how learning with the IWB may be beneficial in the classroom.…”
Section: The Impact Of Interactive Whiteboards On Motivation and Lear...mentioning
confidence: 99%